Design and Development of Information System for Administration and Monitoring of Authentic Deed Services for Notary and Conveyancing Using the Prototyping Method - Rekyahim Rekyahim; Indah Lestari (International ABEC, 2021)
Notary Asep Sudrajat, SH., M.Kn. is a company that provides legal services in making authentic deeds and other legally regulated authorities. Currently, Notary Asep Sudrajat, SH., M.Kn has many requests for authentic deed processing, which is currently the filing process and also for submitting information, clients must come to the office or call the notary to find out the stages of transactions that the client has submitted at this time. The notary must look for files to provide information on the progress of deed processing to clients. Sometimes the delivery of information still occurs problems because the deed completion process takes about 1 to 3 months, this can make it difficult for the notary to find the file. From these problems, an Authentic Deed Service Administration and Monitoring Information System will be built. This information system will be developed based on the website in the notary section with the PHP and MYSQL programming language as the database and the android application will be used by the client. As well as the development method using the prototyping method with 2 iterations. Based on the test results, the system built was in accordance with the requests and needs of the Notary Asep Sudrajat, SH., M.kn. The application also runs well with usability testing with the SUS method resulting in a total value of 84, these results indicate that the application has been accepted by the notary client.